Propaganda and persuasion - Jowett, Garth 1940-; O'Donnell, Victoria (SAGE Publ., 2006)
"Propaganda and Persuasion, Fourth Edition is the only book of its kind to cover a comprehensive history of propaganda and offer insightful definitions and methods to analyze it. Building on the excellence of the three previous editions, the Fourth Edition has been revised, updated, and expanded. Authors Garth S. Jowett and Victoria O'Donnell provide a cogent understanding of persuasion and propaganda, including rhetorical background, cultural studies, and collective memory."--BOOK JACKET.